Longing for Freedom in Sayyid Quthb’s Poem Akhi Anta Hurrun Waraa Al-Sudud - Ahmad Baihaqi; Basuni Imamuddin (Sunan Kalijaga: International Journal of Islamic Civilization, 2019)
A literary work is a repress entation of a character who lived in his time. A literary work usually represents the feelings and conditions of the writer at that time. Among the productive writers was Sayyid Quthb who had a balanced and adequate educational background, both in terms of religious and general education. Sayyid Qutb's life journey significantly changed his outlook. One of his experiences made him join a group to defend the rights of oppressed citizens. One form of his contribution to this cause was writing the poem "Akhi Anta Hurrun Waraa Al-Sudud" to commemorate the events at that time. This article discusses the biography, education, works, and an analysis of sixteen lines from Sayyid Quthb's poem "Akhi Anta Hurrun Waraa Al-Sudud".